Effect of E-Commerce Application, Distribution Management System, and Warehouse Management System in Improving Human Resource Performance - Mudjiyono; Setyani Dwi Lestari; Nora Andira Brabo; Eryco Muhdaliha; Heru Kreshna Reza (Bina Nusantara University, 2022)
Many organizations that run their business processes depend on the individuals within the organization rather than to the system so that problems can occur. If one individual does not exist and consequently hinder the performance of other individuals, such as the example of the division of sales and finance dependence on administration and warehouse divisions. Difficulty serving many customers and many kinds of products, as well as mismatches stock data and reports in real compare by system also raises its own problems in this company. Therefore, the authors are interested in doing research, which this study aims to determine how the effects of the adoption of E-Commerce system, Distribution Management System (DMS), and Warehouse Management system to the performance improvement of human resources in the company Marine Asia Pacific. This study was conducted in individuals who use the system the number of respondents 40 people. The census data collection methods, and data processing using multiple linear regression analysis, assisted with SPSS software version 21. Results of this study showed that the adoption of E-Commerce system, Distribution Management system (DMS), and Warehouse Management system (WMS) had effect on Performance Improvement of Human Resources partially or simultaneously in the MAP company.